THE IMPACT OF MINDFUL LEADERSHIP ON KNOWLEDGE WORKERS’ WORK MOTIVATION - Ling, Xiaohui (Journal of Buddhist Education and Research (JBER), 2024)
In the Internet era, digital office has become the mainstream, and many jobs require employees to have corresponding knowledge and skills. Knowledge workers account for an increasing proportion in enterprises, and how to manage knowledge workers has become one of the key concerns of enterprises. This paper aimed to investigate the status of mindful leadership and characteristics of knowledge workers in China and propose a hypothesis that organizational justice and psychological contract might have a chain mediating effect on the mechanism of mindful leadership and knowledge workers’ work motivation from the perspective of planned behavior theory. Data were collected using a questionnaire, and empirical analysis was conducted based on relevant literature on mindful leadership, sense of organizational justice, psychological contract and knowledge workers’ work enthusiasm. The result revealed that mindful leadership had positive impact on knowledge workers’ sense of organizational justice and psychological contract and could improve knowledge workers’ work enthusiasm. That is, the stronger the leader’s mindful trait is, the stronger the knowledge workers’ sense of organizational justice, psychological contract and work enthusiasm are. Through sample difference analysis, it was found that age and working years significantly affected knowledge workers’ perception of mindful leadership and work initiative, and job position significantly affected knowledge workers’ perception of mindful leadership, organizational justice, psychological contract, and work initiative.